Step
*
1
of Lemma
rv-T'-implies-rv-T
1. n : ℕ+
2. a : ℝ^n
3. b : ℝ^n
4. c : ℝ^n
5. rv-T'(n;a;b;c)
6. a ≠ c
⊢ real-vec-be(n;a;b;c)
BY
{ Assert ⌜∀k:ℕ+. ∃s:ℝ. ((s ∈ ((r(-1)/r(k)), (r(k + 1)/r(k)))) ∧ req-vec(n;b;s*a + r1 - s*c))⌝⋅ }
1
.....assertion..... 
1. n : ℕ+
2. a : ℝ^n
3. b : ℝ^n
4. c : ℝ^n
5. rv-T'(n;a;b;c)
6. a ≠ c
⊢ ∀k:ℕ+. ∃s:ℝ. ((s ∈ ((r(-1)/r(k)), (r(k + 1)/r(k)))) ∧ req-vec(n;b;s*a + r1 - s*c))
2
1. n : ℕ+
2. a : ℝ^n
3. b : ℝ^n
4. c : ℝ^n
5. rv-T'(n;a;b;c)
6. a ≠ c
7. ∀k:ℕ+. ∃s:ℝ. ((s ∈ ((r(-1)/r(k)), (r(k + 1)/r(k)))) ∧ req-vec(n;b;s*a + r1 - s*c))
⊢ real-vec-be(n;a;b;c)
Latex:
Latex:
1.  n  :  \mBbbN{}\msupplus{}
2.  a  :  \mBbbR{}\^{}n
3.  b  :  \mBbbR{}\^{}n
4.  c  :  \mBbbR{}\^{}n
5.  rv-T'(n;a;b;c)
6.  a  \mneq{}  c
\mvdash{}  real-vec-be(n;a;b;c)
By
Latex:
Assert  \mkleeneopen{}\mforall{}k:\mBbbN{}\msupplus{}.  \mexists{}s:\mBbbR{}.  ((s  \mmember{}  ((r(-1)/r(k)),  (r(k  +  1)/r(k))))  \mwedge{}  req-vec(n;b;s*a  +  r1  -  s*c))\mkleeneclose{}\mcdot{}
Home
Index